2020
DOI: 10.9734/jsrr/2020/v26i630271
|View full text |Cite
|
Sign up to set email alerts
|

Cranberry Juice Inhibit Bacterial Pathogens Associated To Urinary Tract Infection

Abstract: Aims: To evaluate in vitro antimicrobial potential of 35% reconstituted juice (RJCr) against bacterial pathogen related to urinary tract infections (UTIs). Place and Duration of Study:  Food and Biotechnology Laboratory, Brazil. Study Design: Cranberry juice for in vitro evaluation by agar well diffusion assay and direct in vitro assay. Methodology: Cranberry fruits were used to produce RJCr pH 3. Five bacterial pathogens were tested: Escherichia coli ATCC 35218, Klebsiella pneumoniae ATCC 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Cranberry standardized extracts and juices, rich in anthocyanidin/proanthocyanidin, demonstrated interesting effects in UTI prevention, as anthocyanidin/proanthocyanidin inhibit the adherence of P-fimbriated Escherichia coli to eukaryotic cells [ 32 ]. More recent studies have also demonstrated the efficacy of products containing Cranberry in inhibiting the in vitro growth of Escherichia coli strains, whereas the same products showed a lower activity compared to other pathogens like Klebsiella pneumoniae , Enterococcus faecalis , Pseudomonas aeruginosa and Proteus mirabilis [ 35 , 36 , 37 , 38 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cranberry standardized extracts and juices, rich in anthocyanidin/proanthocyanidin, demonstrated interesting effects in UTI prevention, as anthocyanidin/proanthocyanidin inhibit the adherence of P-fimbriated Escherichia coli to eukaryotic cells [ 32 ]. More recent studies have also demonstrated the efficacy of products containing Cranberry in inhibiting the in vitro growth of Escherichia coli strains, whereas the same products showed a lower activity compared to other pathogens like Klebsiella pneumoniae , Enterococcus faecalis , Pseudomonas aeruginosa and Proteus mirabilis [ 35 , 36 , 37 , 38 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies report in vitro and in vivo actions towards bacteria and fungi such as Escherichia coli , Klebsiella pneumoniae , Enterococcus faecalis , Pseudomonas aeruginosa , Candida spp., which are among the main microorganisms responsible for UTIs. Moreover, both our and other research groups have previously tested these compounds in vitro as natural extracts, demonstrating that they can exert synergistic activities in combination with the traditional antibiotics or antifungals, or if administered as phytocomplexes [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. For this reason, in the present study, an oral food supplement (OFS) containing extracts from Cranberry and Sweet Chestnut, was formulated and it was tested in vivo on patients with recurrent UTIs.…”
Section: Introductionmentioning
confidence: 99%